A new prostate carcinoma binding peptide (DUP-1) for tumor imaging and therapy - Zitzmann, Sabine; Mier, Walter; Schad, Arno; Kinscherf, Ralf; Askoxylakis, Vasileios; Krämer, Susanne; Altmann, Annette; Eisenhut, Michael; Haberkorn, Uwe (Clinical cancer research, 2005)
PURPOSE: Prostate carcinomas belong to the most widespread tumors, and their number is increasing. Imaging modalities used for diagnosis, such as ultrasound, computed tomography, and positron emission tomography, often produce poor results. Radiolabeled peptides with high sensitivity and specificity for prostate cancer would be a desirable tool for tumor diagnosis and treatment. EXPERIMENTAL DESIGN: We used phage display and the prostate-specific membrane antigen-negative cell line DU-145 to identify a peptide. The isolated DUP-1 was tested in vitro for its binding specificity, kinetics, and affinity. Internalization of the peptide was evaluated with confocal microscopy. The tumor accumulation in a nude mouse model was analyzed with 131I-labeled DUP-1 in PC-3 and DU-145 prostate tumors as well as in the rat prostate tumor model AT-1. RESULTS: The synthesized peptide showed rapid binding kinetics peaking at 10 minutes. It shows specific binding to prostate carcinoma cells but low binding affinity to nontumor cells. Peptide binding is competed with unlabeled DUP-1, and a time-dependent internalization into DU-145 cells was shown. Biodistribution studies of DUP-1 in nude mice with s.c. transplanted DU-145 and PC-3 tumors showed a tumor accumulation of 5% and 7% injected dose per gram, and bound peptide could not be removed by perfusion. The rat prostate tumor model showed an increase of radioactivity in the prostate tumor up to 300% in comparison with normal prostate tissue. CONCLUSIONS: DUP-1 holds promise as a lead peptide structure applicable in the development of new diagnostic tracers or anticancer agents that specifically target prostate carcinoma.